DZIKIR RUH DALAM PERSPEKTIF SYEKH AKBAR MUHAMMAD DAHLAN : (Studi Pemikiran Mursyid ke-2 Tarekat Idrisiyyah di Indonesia) - Dinda Zahra Salsabila; Rizal Fauzi; Luqman Al Hakim (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
Dhikr is a spiritual practice in Islam believed to bring inner peace. However, not everyone who performs dhikr experiences spiritual calm, indicating a problem in its depth or quality. While dhikr has been widely studied, research on dhikr al-rūḥ (dhikr of the soul) as taught by Shaykh Akbar Muhammad Dahlan, the second murshid of the Idrisiyyah Order in Indonesia, remains unexplored. This study aims to examine his concept of dhikr al-rūḥ within the context of the ṭarīqah. Using a qualitative descriptive method with a phenomenological approach, data were collected through interviews with Idrisiyyah practitioners and a literature review. The findings show that dhikr al-rūḥ is a high-level, divinely gifted (mawahib) practice involving spiritual consciousness, rābiṭah with the murshid, and a sanad linking the seeker’s soul to the Prophet Muhammad (peace be upon him). It is not merely verbal repetition, but a gradual process of soul awareness that leads to inner tranquility and spiritual transformation through union with Divine Reality.